Factors of success and failure for transboundary environmental cooperation: projects in the Gulf of Aqaba. Issue 6 (2nd November 2017) - Portman, Michelle E.; Teff-Seker, Yael
ABSTRACT: After signing a peace accord in 1994, joint projects were initiated between Israel and Jordan aimed at enhancing environmental protection and resource management. This paper discusses the Red Sea Dead Sea Canal, the Eilat-Aqaba Municipal Cooperation initiative, the Joint Oil Spill Contingency Plan and the Red Sea Marine Peace Park (RSMPP). The latter is an exemplar of transboundary cooperation for planning of a marine protected area and therefore the main case study. Although the RSMPP never fully materialized, analysis of what transpired provides important lessons. We examine what happened in the 20 years since the attempt to establish the RSMPP began and focus on which of its goals were achieved. As a basis for analysis this paper presents factors identified as significant to the success of transboundary protected areas (TBPAs) and uses them to compare the RSMPP to the three other initiatives. In addition to factors reported in the literature that are known to be effective for TBPA success, we found two new factors as most relevant for the RSMPP case: a peripheral geographic location and intensive work among professionals, mostly marine scientists, on the ground operating under a low profile and with limited public attention.